Portrait of a Contender: Corey Morris - Morris, Corey (Language at Work - Bridging Theory and Practice, 2010)
“Language at Work – Bridging Theory and Practice” caught up with busy Corey Morris on a cold and rainy November day in Denmark. We had two main reasons for looking up Corey at his work. First, we knew that his work takes him to the four corners of the world of branding on a daily basis. Second, we were well aware that Corey would be the right person to ask questions as to where branding is going these days.